Дослідження на території Чернігівського дитинця у 2008 р. - Черненко, О.Є.; Казаков, А.Л.; Печений, Є.В. (Археологічні дослідження в Україні, 2009)
In 2008, the rescue archaeological works on the territory of dytynets (citadel) of Ancient Chernihiv were provided at the area near the Annunciation Church and near the building of Collegium. During the work the new materials for the study of various periods of Chernihiv fortress in the Mediaeval period were obtained.